Cytomegalovirus infection in association with early onset pre-eclampsia. (10th November 2010) - Higgins, L; Vause, S; Tower, C
Abstract : This case describes a woman who presented with raised α-fetoprotein (AFP) on second trimester screening, and developed early onset fetal growth restriction (FGR) and severe pre-eclampsia (PET) before 24 weeks' gestation requiring magnesium sulphate and intravenous antihypertensives. Ultrasonography revealed a structurally normal fetus with estimated weight <3rd centile, abnormal uterine artery Dopplers and deteriorating fetal arterial Dopplers over the following 2 weeks. The pregnancy ended in fetal death before a viable weight was reached. Postmortem examination revealed a growth restricted fetus (birth weight <0.4th centile) and chronic villitis secondary to placental cytomegalovirus (CMV) infection. CMV has previously been associated with PET and FGR. This case highlights its potential role in the pathogenesis of placental failure and has relevance for counselling and management for future pregnancies. Furthermore, raised AFP may represent ongoing placental damage and offers potential for future therapeutic measures—for example, antivirals or immunisations to alter the natural history and prognosis of placental infection.